A wide-speed-range aerodynamic configuration by adopting wave-riding-strake wing. (January 2023) - Feng, Cong; Chen, Shu-sheng; Yuan, Wu; Li, Zheng; Gao, Zheng-hong
Abstract: The wide-speed-range characteristics of aerodynamic configuration are critical to the design of the horizontal take-off and landing aircraft. To address this problem, the work proposes a wide-speed-range aerodynamic configuration by assembling a waverider to the aircraft with arrow-shaped wing. To enhance the aerodynamic performance of this configuration, surrogate optimization method is applied to the airfoil of the arrow-shaped wing. Thus, the optimized airfoil with double "S" cambers on the lower surface, and a small leading-edge radius is obtained. The aerodynamic performance of the whole aircraft in the wide-speed range has been investigated numerically by means of the three-dimensional Reynolds-averaged Navier-Stokes (RANS) equations coupled with the SST k-omega turbulence model. At subsonic conditions, the waverider can act as a strake-wing to induce vortex from the leading edge of the upper surface. With the large sweep arrow-wing, the subsonic aerodynamic performance is improved by utilizing the vortex lift. At supersonic conditions, wave-riding characteristics as well as the small leading-edge radius wing can effectively reduce the wave-drag. Overall, the lift-to-drag ratio of this configuration is not less than 5.4 at 4-degree angle of attack within Mach number 0.5–7, indicating that this configuration provides outstanding hypersonic aerodynamic performance as well as fairly acceptable subsonic aerodynamic characteristics. Highlights: 1. The design method of a wide-speed-range configuration is formulated. 2. The waverider can act as a large-swept strake wing to induce vortices at subsonic speeds. 3. Airfoil optimization is carried out to enhance the aerodynamic performance 4. This configuration provides good hypersonic and acceptable subsonic aerodynamic performance.